Citoinclusão de capa leucocitária e medula óssea de cães: padronização da técnica - Paiva, M. B. [UNESP]; Gouveia, G. M. [UNESP]; Fioravanti, H. [UNESP]; Luvizotto, Maria Cecília Rui [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2014)
The cell block technique is widely used and recognized by health professionals, but lacks in information regarding the specific contribution of this method to veterinary medicine. The cytology of bone marrow and buffy coat (cellular portion of the hole blood) are widely used in the diagnosis of neoplastic and nonneoplastic diseases, and also for the detection of infectious agents. Although the importance of these samples is widely recognized, there is no information about the use of buffy coat and bone marrow samples in the cell block procedure among the research material used for this paper. This work aims for the cell block standardization for canine buffy coat and bone marrow samples. We collected 110 buffy coat samples and 44 bone marrow samples for the cell block preparation, and 68.2% of buffy coat and bone marrow proved to be viable at the end of the procedure. The 95% ethanol fixatives along with the 20 minute processing steps (absolute ethanol, xilol and paraffin, 3 of each) were crucial for the quality of the material both in microtomy and optical microscopy. Mechanical separation of the buffy coat proved to be easy and cheap and was used to compose the cell block technique. In this research we emphasized the importance of cell block standardization in order to develop and easy, inexpensive and reproducible method, regardless of any of the professionals' limitations.
Cell block of canine buffy coat and bone marrow in paraffin blocks: technique standardization
Keywords: dog; cell block; buffy coat; bone marrow; technique